Failed coups, democratization, and authoritarian entrenchment: Opening up or digging in?. Issue 471 (17th November 2018) - Powell, Jonathan; Chacha, Mwita; Smith, Gary E
Abstract: Long maligned as the largest threat to democratization, recent studies have suggested that military coups can act as important windows of opportunity for democratization in authoritarian regimes. It is argued that even failed coup attempts can roughly double the probability that an authoritarian regime democratizes in the next three years. We revisit these findings by assessing each case of a democratic transition occurring in a failed coup spell in Africa, using the standards of prior work. Our analysis points to a more pessimistic view of the influence of failed coups. Specifically, we find that the nature of these transitions, often being drawn out over several years, and the nature of the data previously utilized to test the association undermine the ability to observe a democratizing effect. Instead of failed coups providing a significant boost to democratization, we find they are more likely to reinforce the country's previous political trajectory. Failed coups serve incumbents with the dual benefit of both outing their opponents and providing a pretext for their removal, ultimately providing a policy boost for both democrats and autocrats.